Intraosseous leiomyoma of the calcaneum: An unusual bone tumor of foot and review of literature() - Salunke, Abhijeet Ashok (J Clin Orthop Trauma, 2016)
Leiomyoma is a benign tumor of smooth muscle origin and commonly diagnosed in the uterus, gastrointestinal tract, skin, and mucous membranes. To the best of our knowledge, the only reported intraosseous leiomyomas in extremities occurred in the proximal aspect and distal aspect of the femur, in the tibia, and in the ulna. We are not aware of any previous reports of intraosseous leiomyomas in the foot. The radiograph of the intraosseous leiomyoma shows unilocular or multilocular lytic lesion with sclerotic rim. Due to lack of definitive radiological features on magnetic resonance imaging and computed tomography diagnosis of this rare tumor is established with histopathological study and immuno-histochemistry markers. Smooth muscle spindle cells and positive immunohistochemistry markers for muscle cells is hall mark for the diagnosis. The treatment of intraosseous leiomyoma is surgical intervention by excision with wide margin and curettage followed by filling the cavity. The diagnosis of this tumor is challenging due to its extraordinarily rare incidence. Intraosseous leiomyoma should be included in the differential diagnosis of intraosseous lesion with benign radiographic feature. We report of the first published case of primary intraosseous leiomyoma of calcaneum in a 22-year-old male patient.